2018
DOI: 10.1111/wvn.12323
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Context and Practitioner Attitudes on Implementation of Person‐Centered Assessment and Support for Family Carers Within Palliative Care

Abstract: Implementation may be more successful for services that offer regular opportunities to use the intervention in practice, have sufficient levels of facilitators, stimulate more staff discussion, and encourage maintenance of positive motivation. Implementation of person-centered interventions needs to plan for such factors. This has informed an implementation toolkit for the CSNAT intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…We have previously examined factors affecting the implementation of carer assessment and support more broadly within end-of-life care. 23 25 To better understand particular challenges encountered in this hospital context, we draw upon relevant aspects of the Nonadoption, Abandonment, Scale-up, Spread and Sustainability (NASSS) framework. 26 This framework suggests that sustaining implementation may be very difficult in contexts in which health conditions are unpredictable, where the intervention does not directly measure changes in health condition, and where the intervention does not readily align with prevailing organisation and system beliefs, including what counts as ‘high-quality’ evidence.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously examined factors affecting the implementation of carer assessment and support more broadly within end-of-life care. 23 25 To better understand particular challenges encountered in this hospital context, we draw upon relevant aspects of the Nonadoption, Abandonment, Scale-up, Spread and Sustainability (NASSS) framework. 26 This framework suggests that sustaining implementation may be very difficult in contexts in which health conditions are unpredictable, where the intervention does not directly measure changes in health condition, and where the intervention does not readily align with prevailing organisation and system beliefs, including what counts as ‘high-quality’ evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, around 20 used a deductive approach in that they used the elements and sub-elements to structure the analytic process (e.g., [150,170,188,215,242]). About 35 studies applied PARIHS for quantitative analysis, (e.g., [69,168,174,190,211]). In half of these, the Alberta Context Tool (e.g., [155,165,180,195,229]) and the Organizational Readiness to Change Assessment Tool (e.g., [74,159,219,240]) were used; both these tools being derived from PARIHS.…”
Section: The Application Of Parihs In Data Analysismentioning
confidence: 99%
“…There is often a fear that a new tool might replace or negatively impact the relationship between carer and practitioner, so it is important that any tool is seen as being complementary, and enhancing the therapeutic relationship (Antunes et al, 2014). Diffin et al (2018a) explored the influence of practitioner attitudes on the implementation of the CSNAT. They found that services with a higher proportion of internal CSNAT facilitators to staff members were more likely to be high adopters of the CSNAT, thus being more successful at implementing it.…”
Section: Shared Reviewmentioning
confidence: 99%